Effects of Preparation for Thai Massage Skills before Practicing in Cooperative Education of Health and Spa Science Students - Issarata, Thanaporn; Boonrattana, Nathawarot; Kongkue, Teerapong; Pattakan, Watcharaporn (Journal of Science and Technology Songkhla Rajabhat University, 2024)
This research aimed to study the effects of preparation for Thai massage skills before practicing cooperative education of health and spa science students. The research was divided into two stages: 1) Student preparation stage: 4 students enrolled in the cooperative education preparation course, and the students passed both theoretical and practical assessments. 2) Thai massage service stage in a simulated spa business: 36 volunteers passed the inclusion criteria. Students provided Thai massage, foot massage, and therapeutic massage for volunteers. It found that the students were able to reduce the pain of volunteers after treatment significantly in all three groups compared to before treatment, and compared with a mean reduction in pain in all three groups with no difference. The satisfaction of Thai massage services found that the volunteers were most satisfied, which supported that the students had Thai massage skills and service skills. A study of the relationship between personal factors and the level of satisfaction found that there was no relationship. Therefore, preparation in theory and practice in real situations can improve Thai massage skills and build confidence before going out to work in the workplace.